VLOG MATEMATIKA MATERI HIMPUNAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA SMP KELAS VII - Lestari, Alia; Nuratiqah, Nuratiqah; Ihsan, Muhammad (Kadikma, 2022)
This study aims to produce valid and practical math vlogs for set material to increase the learning interest of seventh-grade junior high school students. The development method used is the 4D model, which consists of 4 stages: define, design, develop, and disseminate. Material experts and media experts measured the validity of the vlogs, while practicality was obtained from practicality questionnaires from teachers and students. The increase in students' interest in learning was measured by an interest in learning questionnaire given before and after watching the developed mathematics vlog. The research results show that the developed math vlog meets valid, practical and effective criteria to increase students' interest in learning.